Abnormal microRNA expression profile at early stages of gestation in pregnancies destined to develop placenta previa - Hromadnikova, Ilona; Kotlabova, Katerina; Krofta, Ladislav (Frontiers in Medicine, 2024)
Background: Placenta previa, abnormal implantation of the placenta into the lower segment of the uterus, is associated with adverse maternal and fetal outcomes such as placenta accreta spectrum disorders, antepartum and postpartum haemorrhage, fetal growth restriction, prematurity, stillbirth and neonatal death, thrombophlebitis, and septicaemia. The aim of the study was to assess retrospectively how later onset of placenta previa affects microRNA expression profile in the whole peripheral blood at the first trimester of gestation. Methods: Regarding occurrence of the association between aberrant microRNA expression profiles at early stages of gestation and later onset of various pregnancy-related complications, we selected for the study pregnancies developing placenta previa as the only one pregnancy-related disorder. 24 singleton pregnancies diagnosed with placenta previa undergoing first trimester prenatal screening as well as delivering on site within the period 11/2012-5/2018 were included in the study. 80 normal pregnancies delivering appropriate for gestational age newborns after completed 37 weeks of gestation selected based on the equality of the length of biological sample storing were involved as the control group. Results: Down-regulation of multiple microRNAs (miR-20b-5p, miR-24-3p, miR-26a-5p, miR-92a-3p, miR-103a-3p, miR-130b-3p, miR-133a-3p, miR-145-5p, miR-146a-5p, miR-155-5p, miR-181a-5p, miR-195-5p, miR-210-3p, miR-342-3p, and miR-574-3p) was observed in pregnancies destined to develop placenta previa. The combination of seven microRNAs (miR-130b-3p, miR-145-5p, miR-155-5p, miR-181a-5p, miR-210-3p, miR-342-3p, and miR-574-3p) showed the best accuracy (AUC 0.937, p< 0.001, 100.0% sensitivity, 83.75% specificity) to differentiate at early stages of gestation between pregnancies with normal course of gestation with and without the presence of placenta previa diagnosed in the second half of pregnancy. 75.0% pregnancies destined to develop placenta previa was correctly identified at 10.0% FPR. Conclusions: Consecutive large-scale analyses must be performed to verify the reliability of the proposed novel early predictive model for placenta previa occurring as the only one pregnancy-related disorder.